Depresión y conducta suicida en estudiantes adolescentes de la Institución Educativa Colegio Nacional de Iquitos 2024 - Vega Guerra, Seymi Suellen (2025)
The objective of the study was to determine the relationship between depression and suicidal behavior in third-year high school students at the Colegio Nacional de Iquitos 2024 educational institution. The research was quantitative, non-experimental, correlational, cross-sectional, in a sample of 85 adolescents aged 12 to 15 years. The technique used was a survey, and two instruments were applied: Zung’s Self-Rating Depression Scale and Beck’s Scale for Suicidal Ideation. The results showed that 34.1% did not present depression, while 65.9% presented depression; among them, 44.7% had mild depression and 21.2% moderate depression. Furthermore, 77.6% of adolescent students presented suicidal behavior, while 22.4% did not. By applying the Chi-square test (χ²), a value of X² = 19.07; gl = 2; p = 0.001; α = 0.05 was obtained, showing statistical significance. In conclusion, there is a statistically significant relationship between the level of depression and suicidal behavior (p = 0.001; α = 0.05) in adolescent students at the Colegio Nacional de Iquitos in 2024.